Legal Protection For Capital Market Investors Regarding Confiscation of Public Company Shares Due to Criminal Acts Committed by the President Director (Case Study of PT Hanson International TBK) - Saputra, Angga (SEAN Institute, 2025)
This study discusses legal protection for investors for the confiscation of public company shares due to criminal acts committed by the company's president director and legal protection for capital market investors when the public company invested is declared bankrupt. The research method used is normative legal research, which is research that examines document studies, using various secondary data such as legislation, legal theory, books, journals, and other legal sources. The approach method used are a statutory, conceptual, and case approach. This study found that legal protection for investors must be carried out because the confiscation of shares and assets of PT Hanson deviates from the application of the rule of law to Article 39 paragraph (1) of Law Number 8 of 1981 concerning the Criminal Procedure Code because the confiscated shares and assets do not have a direct relationship with criminal acts committed by the president director. Article 31 paragraph (2) of the Law states, all confiscations are stopped when the bankruptcy decision has been pronounced, if necessary the supervisory judge must order the cancellation. Since the bankruptcy decision is pronounced, all confiscations on an object expire and are replaced with general bankruptcy confiscations. Legal protection for investors in public companies that are declared bankrupt can be carried out with preventive and repressive legal protection.